DAMPAK PENGESAHAN PERPPU CIPTAKER DALAM UNDANG-UNDANG NOMOR 6 TAHUN 2023 DITINJAU BERDASARKAN SYARAT BERAKHIRNYA PERATURAN PERUNDANG-UNDANGAN - POTUTU, ZUNAID (Ganec Swara, 2025)
The impact of the ratification of the Job Creation Perppu into Law Number 6 of 2023 is very significant, especially in the context of the expiration of statutory provisions. Based on the decision of the Constitutional Court (MK) Number 91/PUU-XVIII/2020, the previous Job Creation Law was declared conditionally unconstitutional, with two years for substantial improvements. However, the government issued a Perppu on Job Creation which was later passed into law even though there was still time to make improvements. From a Sociology of Law perspective, this ratification shows dissatisfaction with the process of public participation and freedom of opinion, which are important conditions in the formation of legitimate and accepted laws. Research shows that Perppu No. 2 of 2022 which was amended into Law No. 6 of 2023 did not meet the requirements of compelling urgency stipulated in the law, thus raising questions about the legitimacy of the law and in the fairness of the legislative process.Overall, the ratification of the Job Creation Law creates challenges in the harmonization and synchronization of existing regulations, especially related to the rules of law formation stipulated in Law No. 12 of 2011. This suggests the need for further evaluation to ensure that the resulting law truly reflects the needs of society and the prevailing legal principles.